Essays on Turkish private hospital industry :|dynamics of market structure, health reforms and regulations - Boyacı, İsrafil. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This thesis consists of three essays on empirical industrial organization. The first chapter focuses on the hospital industry environment in Turkey, provides a comprehensive picture of the industry, and also sets the foundation for the following chapters. The descriptive empirical analysis, which covers a period when the private hospital market nationwide experienced considerable growth, provides an insightful description of the hospital industry in Turkey while comparatively investigating and discussing the change in the competitive and regulatory environment with the health reforms implemented under the Health Transformation Program 2003-2013 (HTP). The second chapter addresses hospital entry and competition by employing a panel dataset on hospitals and local market characteristics. The static model builds on the entry threshold method of Bresnahan and Reiss (1988, 1990, 1991). Besides explaining the proliferation of private hospitals nationwide during the HTP in local districts of Turkey over the sample period 2001-2014, the multi-period estimations help explore the overall role of the health reforms and regulations under the HTP in shaping the hospital market structure. The third and final chapter of the research analyzes the capacity choices of hospitals in the post-reform period after 2010 with the help of a stochastic strategic investment model in an oligopoly game setting. The equilibrium solution of the theoretical model and empirical analysis provides evidence for the discussion of whether the private hospitals in Turkey engage in a medical arms race in the form of strategic capacity accumulation due to the local competitive pressures on them.
Keywords: Hospitals -- Turkey.; Hospitals -- Economic aspects -- Turkey.; Health services -- Turkey.; Hospitals, Proprietary -- Turkey.